A Guidebook to the museums of Visayas - Mayhow, Mary Jane Calderon; Deiparine, Marilou R. (Manila National Commission for Culture and the Arts, 1992)
The guidebook covers 31 different museums from the nine provinces in the Visayas. Each museum contains a historical collection and contact details. It is full of good illustrations and photos. It also contains maps.
Keywords: Museums -- Philippines -- Visayas